Quality analysis of coffee waste compost with the addition of cassava tapai local microorganism (LMO) bioactivator - Sukmawati, Fitria Nugraheni; Irna, Afifah; Pramudya, Yudhi; Sukarji, Sukarji; Pamungkas, Saktiyono Sigit Tri; Rahmat, Ali; Rozaki, Zuhud; Hanum, Farrah Fadhillah (Research and Social Study Institute, 2023)
Coffee waste contains a large amount of nutrients, making it a potential raw material for compost fertilizer. The nutrients contained in coffee waste include N, P, K, Mg, and Ca. Utilization of coffee waste as compost requires bioactivators to accelerate the decomposition process. This study aims to determine the difference in compost quality from coffee waste by using bioactivators in the form of local microorganisms (LMO) of cassava tapai. This study was conducted from April to May 2023 at the greenhouse of LPP Polytechnic Yogyakarta, consisting of two stages: making the LMO and making the compost. Cassava tapai LMO was prepared as a treatment for composting coffee waste. Each treatment was repeated three times. After that, the fermentation results in the form of compost were tested, then the results were compared with the standards of the Decree of the Minister of Agriculture No. 261/KPTS/SR.310/M/4/2019 on the minimum technical requirements for organic fertilizers, biological fertilizers, and soil conditioners. The results reveal that the provision of cassava tapai LMO bioactivator affected the quality of coffee waste compost produced. The quality of composts produced from control, cassava tapai LMO of 90 ml, and EM-4 treatment does not meet the standards of the Decree of the Minister of Agriculture in the parameter of chemical properties, namely the C/N ratio. The quality of compost produced from cassava tapai LMO of 120 ml meets the standards of the Decree of the Minister of Agriculture and SNI 2004 in all parameters of physical properties, chemical properties, and nutrient content.